Effect of mass of solid and soaking effect on chemical component of physalis minima linn by solvent-free microwave extraction (SFME) - Md Nor, Nadirah (2019)
Essential oils extraction from Physalis minima Linn plant was performed by using solventfree microwave extraction (SFME) method. The aim of this research is to study the effect of mass of solid and soaking effect on chemical component were studied. The mass of solid and soaking days applied in this research are 4,6,8,10 g and 1,2,3 days respectively. GC-MS was used in determination of chemical components in the essential oils. It is found that the main constituents identified in relative higher abundance is 9,19-Cyclolanost-24- en-3-ol, acetate or known as Cycloartenol acetate (C₃₂H₅₂O₂). The optimum parameters for mass of solid and soaking days are 8 g and 1 day sccordingly. This is because the selected active compound for mass of solid experiment which is Cycloartenol acetate and for soaking experiment Diethyl acetal (C₆H₁₄O₂) are found highest in abundance. Therefore, it is demonstrated that the SFME method is an excellent alternative for extraction of essential oils from P. minima and other type of plant.